A Specific IFIH1 Gain-of-Function Mutation Causes Singleton-Merten Syndrome - Rutsch, Frank; MacDougall, Mary; Lu, Changming; Buers, Insa; Mamaeva, Olga; Nitschke, Yvonne; Rice, Gillian I.; Erlandsen, Heidi; Kehl, Hans Gerd; Thiele, Holger; Nürnberg, Peter; Höhne, Wolfgang; et al. (American journal of human genetics, 2015)
Singleton-Merten syndrome (SMS) is an infrequently described autosomal-dominant disorder characterized by early and extreme aortic and valvular calcification, dental anomalies (early-onset periodontitis and root resorption), osteopenia, and acro-osteolysis. To determine the molecular etiology of this disease, we performed whole-exome sequencing and targeted Sanger sequencing. We identified a common missense mutation, c.2465G>A (p.Arg822Gln), in interferon induced with helicase C domain 1 (IFIH1, encoding melanoma differentiation-associated protein 5 [MDA5]) in four SMS subjects from two families and a simplex case. IFIH1 has been linked to a number of autoimmune disorders, including Aicardi-Goutières syndrome. Immunohistochemistry demonstrated the localization of MDA5 in all affected target tissues. In vitro functional analysis revealed that the IFIH1 c.2465G>A mutation enhanced MDA5 function in interferon beta induction. Interferon signature genes were upregulated in SMS individuals’ blood and dental cells. Our data identify a gain-of-function IFIH1 mutation as causing SMS and leading to early arterial calcification and dental inflammation and resorption.